Diversity, diagnosis and phylogeny of genus Aphelenchoides (Aphelenchoidea:Nematoda), whith focus on the plant-parasitic species - Sánchez-Monge, Gerardo Alcides (2016)
UCR::Rectoría::Oficina de Asuntos Internacionales y Cooperación Externa (OAICE)